Rancang Bangun Sistem Persediaan Dan Distribusi Sepeda Motor Menggunakan Metode FIFO - Marisa . (KILAT, 2019)
Motorbikes supply and distribution is one of the important work activities for the development of PT. Jagat Karya Abadi. In its development, there are many problems arise, such as the difficulties of obtaining fast, precise and accurate inventory information. As for the emergence of these problems is the frequent occurrence of errors in recording motorbike data entry, motorbike demand and motorbike expenditure until the making of reports.The use of technology and computerization are have a big contribute so the tasks and work are carried out properly. It aims to avoid and reduce errors in recording, lack of accuracy, and others. Motorbikes supply and distribution system at PT. Jagat Karya Abadi with the FIFO method is one solution to overcome existing problems. The inventory and distribution system at PT Jagat Karya Abadi implements PHP programming languages, database and MySQL.